Morphometric analysis of sphenoid sinus in patients with nasal septum deviation - Orhan, İsrafil; Örmeci?, Tuğrul; Bilal, Nagihan; Sağıroğlu, Saime Güzelsoy; Doğaner, Adem (Lippincott Williams and Wilkins, 2019)
This retrospective study aimed to assess the association of the volume and types of the sphenoid sinus with deviated nasal septum by analyzing multislice computed tomography images. A total of 93 patients with a deviated nasal septum and 70 healthy controls were included in the study. Patients with sinonasal morbidities other than deviation were excluded. Three-dimensionally reconstructed computed tomography images of the study participants were acquired. A total of 326 sphenoid sinus volumes from the patient and control groups were obtained and compared between the groups. Sphenoid sinus volumes and the angle of the deviation were measured for standardization and assessment of the severity. Deviated nasal septum was found on the right in 49.5% (n=46) and on the left in 50.5% (n=47) of the study participants. Deviation angles were in the range from 7.28 to 22.48 and the mean value was 13.28±5.08. The measured volumes were in the range from 1.8 cm3 to 9.6 cm3 with a mean of 4.8±1.5 cm3. In the control group, the median values for the sphenoid sinus volumes were 4.40 cm3 (0.80- 8.90 cm3) on the right and 4.20 cm3 (0.90-8.70 cm3) on the left. In the study group, sphenoid sinus volumes were found to be statistically significantly different between those on the ipsilateral and contralateral side of the septal deviation. Sphenoid sinus volumes were significantly smaller on the same side with septal deviation compared with those on the contralateral side. There was no statistical relationship between the presence of septal deviation, age and gender, and the type of sphenoid sinus.
Keywords: Septal Deviation; Sphenoid Sinus Type; Sphenoid Sinus Volume; Three-Dimensional Imaging